Concordance of 24-h intraocular pressure curve in patients with untreated unilateral primary open-angle glaucoma - Lin, Zhongjing (Exp Ther Med, 2018)
The present study aimed to assess the concordance of 24-h intraocular pressure (IOP) curves between glaucomatous and contralateral eyes for patients with untreated unilateral primary open-angle glaucoma (POAG). A total of 32 patients with unilateral POAG and 32 age-matched normal subjects were enrolled. The IOP measurements were performed every 2 h over a 24-h period. The concordance of the 24-h IOP curves was assessed via the correlation coefficient (r), intraclass correlation coefficient (ICC) and repeated-measures analysis of variance (ANOVA). No significant difference was identified between all IOPs, as well as the mean, peak and trough IOP or IOP fluctuations of the paired eyes in the two groups. The strength of association of all IOPs was moderate in the glaucoma group (r, 0.752-0.867) and the normal controls (r, 0.625-0.873). IOP readings at each time-point indicated a high agreement in the glaucoma group (ICC, 0.857-0.929) and the normal controls (ICC, 0.768-0.932). Repeated-measures ANOVA indicated that the 24-h IOP curves of the paired eyes had parallel profiles in the two study groups (P=0.837 and P=0.897, respectively). The glaucoma patients had significantly higher proportions of all IOPs displaying absolute differences of ≥2 and ≥3 mmHg (46.09 vs. 35.68%, P<0.001; 29.69 vs. 12.50%, P<0.001, respectively). In conclusion, the 24-h IOP curves of the paired eyes had parallel profiles in unilateral glaucoma patients and normal subjects. However, unilateral glaucoma patients had a significantly larger proportion of IOP differences of ≥2 and ≥3 mmHg.